THE POTENTIAL DEVELOPMENT STRATEGY OF PESANTREN LITERATURE TO SUPPORT A RELIGIOUS TOURISM TOWARDS A CREATIVE INDUSTRY - Faridi, Abdurrachman (Universitas Negeri Semarang, 2011)
PesantrenÃ¢â‚¬â„¢s literature is a cultural treasure which exists in Indonesia. PesantrenÃ¢â‚¬â„¢s enchantment can be viewed from many sides; i.e. environment, education, teaching, human, even customs and arts. These conditions provide a variety of potential to be optimized. The aim of this study is to expose the potential and model of pesantrenÃ¢â‚¬â„¢s literature to support religious tourism as a creative industry. The result of this study is to optimize the potential development strategy of pesantrenÃ¢â‚¬â„¢s literature and to support religious tourism as a creative industry. PesantrenÃ¢â‚¬â„¢s literature is used as one of religious tourism attractions that brings the economic life towards a creative industry, and to create other economic activities beneficial for the grassrootsÃ¢â‚¬â„¢ level. Ã‚Â Keywords: pesantrenÃ¢â‚¬â„¢s literature, religious tourism, creative industry